Role of intellectuals in the fiction of Xiao Hei - Chia, Mei Shi (2018)
Intellectuals are expected to have a certain degree of knowledge and take up the social responsibility as well. They are also having independent personality and critical spirit. Malaysian Chinese writer, Xiao Hei had the opportunity to create some local works due to the political relaxation before and after the 1990s. Xiao Hei had included the catastrophic themes of history and politics in his novels. Intellectuals are important characters in the works of fiction of Xiao Hei. This study aims to sort out and examine the intellectuals in the works of fiction of Xiao Hei according to Edward Said and Antonio Gramsci's conception of the intellectual, and also refer to the actual situation in Malaysia. Also, Xiao Hei’s reflection and examination on these intellectuals are discussed according to the social role and fate of intellectuals in his works of fiction. In his works of fiction, the intellectuals are adhered to the different state of mind and they have made different choices in the different state of survival and social context. Different types of intellectuals reflect different ethos.